Genetic variability and performance of Asian swamp eel Monopterus albus (Zuiew, 1793) from West Java cultured in saline water medium - Soelistyowati, Dinar Tri; Syarif, Ahmad Fahrul; Affandi, Ridwan; Hidayatullah, Dendi (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT  Asian swamp eel Monopterus albus (Zuiew, 1793) is freshwater fish species which is prospective for domestic and export markets. The production is limited depend on the catches of natural population. The cultivation of eel has been carried out to increase the production for sustainability. This study was conducted to evaluate the genetic variability and performance of Asian swamp eel from West Java and its potential cultivation in water based media with salinity. Three populations from West Java were collected of different altitudes from Sukabumi (673 m asl), Cianjur (429 m asl), Karawang (51 m asl) sized 19–26.5 cm and weighed 4.95–11.4 g. The cultivation was performed during 30 days in water media without substrate at salinity 6 ppt with density of 1 kg/m2 and maintenance at container 50×30×30 cm completed with shelter pipe of ¾ inches diameter and 20 cm length, height of water 10 cm and water exchange 100% every day, fed at satiation using Tubificidae once a day. Genetically, all of the populations showed low heterozygosity at 1.19–1.23% and genetic distance 0.01–0.04. Asian swamp eel adapted better at water salinity 6 ppt which indicated by low mesure of osmotic gradient and blood glucose. Asian swamp eel from Karawang showed superior at survival rate (90%) and daily growth rate (1.42/day). Keywords: Asian swamp eel, Monopterus albus, cultivation, genetic variability, salinity  ABSTRAK  Belut sawah Monopterus albus (Zuiew, 1793) merupakan komoditas ikan air tawar potensial di pasar domestik maupun ekspor, namun produksinya masih mengandalkan hasil tangkapan dari alam karena budidaya belum berkembang. Penelitian ini bertujuan untuk mengevaluasi keragaman genetik dan keragaan belut sawah asal Jawa Barat dan potensinya untuk dikembangkan dengan teknik budidaya di air bersalinitas tanpa lumpur. Tiga populasi belut sawah dikoleksi dari lokasi di Jawa Barat dengan ketinggian berbeda yaitu Sukabumi (673 m dpl), Cianjur (429 m dpl), Karawang (51 m dpl). Sumber genetik belut berukuran 19–26,5 cm dan bobot berkisar 4,95–11,4 g dipelihara selama 30 hari dalam media air tanpa substrat bersalinitas 6 ppt. Wadah pemeliharaan berukuran 50×30×30 cm dilengkapi shelter pipa paralon diameter ¾ inci dan panjang 20 cm serta ketinggian air 10 cm. Padat penebaran ikan 1 kg/m2 (20 ekor/wadah), serta pergantian air 100% dilakukan setiap hari dan pemberian pakan berupa Tubificidae secara at satiation satu kali sehari. Secara genetik ketiga populasi menunjukkan tingkat heterosigositas yang rendah yaitu berkisar 0,19–0,23 % dan jarak genetik 0,01–0,04. Belut sawah menunjukkan respons adaptasi yang baik dalam media air tanpa substrat pada salinitas 6 ppt berdasarkan indikator beban osmotik dan kadar glukosa yang rendah. Belut sawah asal Karawang unggul pada laju pertumbuhan harian (1,42/hari) dan kelangsungan hidup (90 %). Kata kunci: belut sawah Monopterus albus, budidaya, keragaman genetik, salinitas